Efektivitas Model Pembelajaran Jigsaw Terhadap Hasil Belajar IPS Ditinjau Dari Motivasi Dan Fasilitas Belajar - Kholifatuz Zuhroh; Ninik Indawati; Onik Farida Ni’matullah (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to analyze the effectiveness of the Jigsaw learning model on Social Sciences (IPS) learning outcomes reviewed from the motivation and learning facilities of elementary school students. The approach used is quantitative with the type of explanatory research. The research population included 80 grade IV students of SDN Cluster IV, Gading District, Probolinggo Regency. Data collection was carried out through learning outcome tests and motivation questionnaires as well as learning facilities using the Likert scale. Data analysis uses multiple linear regression to determine simultaneous and partial influences between variables. The results showed that the Jigsaw learning model, learning motivation, and learning facilities had a significant effect on social studies learning outcomes of students. The determination coefficient of 0.682 indicates that 68.2% of the variation in learning outcomes is explained by these three variables. Students who have high motivation and are supported by adequate learning facilities show better improvement in learning outcomes after the implementation of the Jigsaw model. These findings prove that the Jigsaw model is effectively applied in social studies learning because it encourages active engagement, individual responsibility, and group cooperation. This study recommends that teachers implement a cooperative learning model consistently with the support of adequate facilities to improve the quality of social studies learning in elementary schools.